2020
DOI: 10.1080/23311886.2020.1787695
|View full text |Cite
|
Sign up to set email alerts
|

Gender, sexual orientation and health behaviors in the ELSA-Brasil cohort

Abstract: This study aimed to investigate differences in health behaviors as a function of gender and sexual orientation in the ELSA-Brasil cohort. Data were collected using a multidimensional questionnaire on health-related behaviors. The sample consisted of 10,314 participants, each of whom was in a stable relationship. Individuals in same-sex relationships were more likely to smoke, to spend more of their leisure-time in front of a screen and to sleep longer. When the behaviors were analyzed as a function of sexual o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…There is a growing demand for the inclusion of sexual orientation in population surveys to enable the monitoring of disparities related to this aspect 18 . Although there is already an increasing literature on health issues of the LGB population, there is a concentration of studies conducted in the United States and in European countries 9,[19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing demand for the inclusion of sexual orientation in population surveys to enable the monitoring of disparities related to this aspect 18 . Although there is already an increasing literature on health issues of the LGB population, there is a concentration of studies conducted in the United States and in European countries 9,[19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Population-based surveys, using probabilistic samples, which simultaneously address the sexual orientation and health of the population are scarce in countries such as Brazil. Existing studies dealing with this topic often involve convenience samples, focuses on specific regions of the country, or only include LGB people 21,27,28 . On the topic of mental health and substance use, the only national-level study identified examined only substance use without stratification by sex 23 .…”
Section: Introductionmentioning
confidence: 99%